Cellulase production, simultaneous saccharification and fermentation in a single vessel: A new approach for production of bio-ethanol from mild alkali pre-treated water hyacinth. Issue 3 (June 2017) - Narra, Madhuri; Divecha, Jyoti; Shah, Disha; Balasubramanian, Velmurugan; Vyas, Bipin; Harijan, Manisha; Macwan, Kumud
Highlights: Bio-ethanol production from water hyacinth in a single reactor. Inverted cone frustum type in-house designed pretreatment reactor. Enhanced ethanol yields by addition of pectinase from water hyacinth. Abstract: The current paper reports on-site cellulase production followed by simultaneous saccharification and fermentation (SSF) of pre-treated water hyacinth for ethanol production in the same flask. Pre-treatment was carried out with 0.5% (w/v) NaOH at room temperature (RT) and 121 °C for 24 h and 30 min, respectively. SSF studies were performed with Kluveromyces marxianus (42 °C) and Saccharomyces cerevisae (30 °C) at 8% solids loading (w/v). RT and 121 °C pre-treated water hyacinth yielded maximum ethanol concentration of 7.32, 8.04 and 5.21, 5.98 g L −1 after 48 h at 42 and 30 °C, respectively. On 8th day, crude cellulases were supplemented with commercial pectinase. Supplementation of pectinase yielded 1.04 to 1.11 fold higher ethanol yields as compared to without pectinase flasks. The current ethanol yields were achieved at higher solid loadings in a single flask by avoiding number of steps/flasks as required in the conventional process.